Factors influencing acceptance of family planning methods among women coming to immunization OPD: a cross sectional study - Wasekar, Sneha A.; Shaikh, Uzma A. (International Journal Of Community Medicine And Public Health, 2023)
Background: Family planning is one of the most cost-effective interventions. Therefore, different factors influencing reasons behind non acceptance of family planning are necessary to be known in order to formulate good plans and policies. Methods: This study was a cross-sectional study conducted at immunization clinic of urban area. Systematic random sampling method was used. A pre-determined questionnaire was administered. Data was analysed using SPSS 22. Results: Only 42.63% women adopted family planning methods. The statistically significant predictors for uptake of family planning services are knowledge of contraceptives (p=0.000), school education (p=0.002), prior use of contraceptives (p=0.001) and age of mother. The reasons for non-acceptance of family planning practices were fertility related (21.2%), lack of knowledge (19.7%), opposition from family members (16.9%), breastfeeding (14.5%), not having intercourse (12%), method related side effects (8.5%) and preference to specific gender (2.1%). Conclusions: According to age group and number of children to women should be motivated by the health worker for the appropriate contraception choice and reasons for non-acceptance of family planning methods form the basis for the qualitative research studies.